Covid 19 And Its Implications on Climatic Change - A Review - GEORGE, RINKI; ANJALI, A.K; ROY, ANITHA (The journal of contemporary issues in business and government, 2020)
COVID 19 is due to SARS-CoV2 and has a vital role as a causative agent of a potentially fatal disease which targets the human respiratory system. Generalized additive models are used to explore the effect of diurnal temperature, humidity on COVID 19. COVID 19 has played a crucial role in revitalizing the Earth causing enticed changes worldwide. Efforts have been made to prioritize investments for adopting a shift to cleaner energy alternatives, thereby sustaining human lives. COVID 19 has a positive impact on the global climatic conditions making it favorable for the inhabitants. There is a significant reduction in the level of greenhouse gas emissions, the use of fossil fuels, coal, non-renewable resources, relative humidity, air pollution. The global calamity has led to a serious threat to human lives. To control the pandemic, special attention and efforts are taken to protect the person-to-person transmission. Social distancing must be maintained to prevent the spread of the disease. The only treatment option available is using broad-spectrum antiviral drugs such as nucleoside analogs and also HIV-protease inhibitors that can alter the viral infection until the special antiviral agents are invented. The study aims to explore the associated climatic changes due to COVID-19.